THE STUDY OF HELICOVERPA ARMIGERA (HÜBNER) AND SPODOPTERA EXIGUA (HÜBNER) BIOLOGICAL LIFESTYLES IN ARMENIA - H.L. Terlemezyan,; M.H. Ghazaryan, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
In 2021-2022, studies on the biological lifestyle of Helicoverpa armigera (Hübner) and Spodoptera exigua (Hübner) were carried out in the pepper fields of Khoronk community, Armavir marz, Republic of Armenia. As a results show that the flight of the adults of Spodoptera exigua (Hübner) starts from the third ten days of May to the third ten days of June. Females lay eggs in piles on the upper and lower surfaces of pepper leaves. She lays 87-173 eggs in each pile. The newly hatched larvae feed on the leaves, causing them to ossify, while the mature larvae feed on the fruit, entering the fruit and feeding on the seeds. After finishing feeding, they descend into the ground and mate at a depth of 2-6 cm. Spodoptera exigua (Hübner) overwintering in the soil in the puporial stage. It develops in 2-3 generations during vegetation. The flight of adults of Helicoverpa armigera (Hübner) starts from the first ten days of June and continues until the third ten days of June. Females lay eggs in small piles on the leaves, buds, and stems of pepper, laying 5-7 eggs in each. Each female can lay 396-472 eggs during her lifetime. The newly hatched larvae first feed on the flowers or flower buds, then move onto the leaves and start feeding on the leaves. Mature larvae feed on fruits. As a result of damage, the fruits lose their marketable appearance and rot. After completing the development, the larvae descend to a depth of 4-11 cm into the soil and pupation. The Helicoverpa armigera (Hübner) overwinters in the puporial phase. It develops in 2 generations per year in the pepper fields.